Effect of fish oil and vitamin E on sperm lipid peroxidation in dogs - Risso, Analía Lorena (2017)
The objective was to evaluate the effects of dietary fish oil (FO) and vitamin E (VE) supplementation on sperm sensitivity to lipid peroxidation (LP) in dogs. Using an incomplete replicate 3 × 3 Latin square design, five dogs were allocated into three groups. One of the squares was incomplete and had two dogs that were used with three treatments. The dogs were assigned to three different treatments, fed a control diet of balanced commercial food (control group; CG), control diet supplemented with 54 mg FO/kg body weight0·75 per d (FO group; FG) and FO plus 400 mg VE per d (FO and VE group; FEG) for 60 d. Semen samples were collected on days 0 and 60 and divided into two halves, peroxidised and control, with or without ascorbate–Fe2+, respectively. LP was measured in both halves by chemiluminescence as counts per min/mg protein. Fatty acid profile was determined by GC. Data were analysed using the mixed procedure (SAS). On day 0, LP increased in all groups in the peroxidised samples (P < 0·05). However, on day 60 LP decreased in peroxidised samples of both the FG and FEG (P < 0·05), but there were no differences between the FG and FEG (P > 0·1). Additionally, on day 60 total n-3 was higher in the FG and FEG compared with the CG (P < 0·05). Supplementation with FO alone or together with VE decreased LP in peroxidised samples. These results could indicate a protective effect of n-3 on sperm. More studies are needed to understand the mechanism whereby FO and/or FO plus VE decrease LP in dogs’ sperm.